Rheumatoid Arthritis-Associated Orbital Vasculitis. Issue 5 (September 2018) - Weber, Adam C.; Shetlar, Debra J.; Yen, Michael T.
Abstract : A patient with a history of rheumatoid arthritis presented with bilateral orbital lesions while on abatacept. Biopsy of the lesions yielded pathologic assessment showing vasculitis with a mixed inflammatory infiltrate notable for numerous eosinophils. Despite initial improvement on cyclophosphamide therapy, she developed progression of the orbital lesions and lesions elsewhere on her body. All serologic studies were normal except for increased levels of rheumatoid factor and eosinophilia. The patient underwent a second biopsy, which was consistent with her initial pathology. The patient was started on high-dose mycophenolate mofetil treatment with a good response. After 1 year of treatment, the patient's lesions have nearly completely resolved. This patient illustrates the diagnostic and therapeutic challenges encountered when treating orbital vasculitis. Furthermore, this case shows the importance of not categorizing vasculitis with unclear etiology under the umbrella diagnosis of atypical granulomatosis with polyangiitis. This patient did not exhibit the serologic or pathologic characteristics of granulomatosis with polyangiitis, and she did not respond to treatment as would be expected for granulomatosis with polyangiitis. Maintaining an open approach to diagnosis and treatment was crucial in obtaining a favorable outcome for this patient. Abstract : The authors present a patient with rheumatoid arthritis-associated orbital vasculitis who challenged the standard diagnostic and therapeutic approach to orbital vasculitis.